Constraints on the distances and timescales of solid migration in the early solar system from meteorite magnetism - Bryson, JFJ; Weiss, B; Biersteker, J; King, A; Russell, S (American Astronomical Society, 2020)
The migrations of solid objects throughout the solar system are thought to have played key roles in disk evolution and planet formation. However, our understanding of these migrations is limited by a lack of quantitative constraints on their timings and distances recovered from laboratory measurements of meteorites. The protoplanetary disk supported a magnetic field that decreased in intensity with heliocentric distance. As such, the formation distances of the parent asteroids of ancient meteorites can potentially be constrained by paleointensity measurements of these samples. Here, we find that the WIS 91600 ungrouped C2 chondrite experienced an ancient field intensity of 4.4 ± 2.8 μT. Combined with the thermal history of this meteorite, magnetohydrodynamical models suggest the disk field reached 4.4 μT at ~9.8 au, indicating that the WIS 91600 parent body formed in the distal solar system. Because WIS 91600 likely came to Earth from the asteroid belt, our recovered formation distance argues that this body previously traveled from ~10 au to 2–3 au, supporting the migration of asteroid-sized bodies throughout the solar system. WIS 91600 also contains chondrules, calcium-aluminum-rich inclusions and amoeboid olivine aggregates, indicating that some primitive millimeter-sized solids that formed in the innermost solar system migrated outward to ~10 au within ~3–4 Myr of solar system formation. Moreover, the oxygen isotopic compositions of proposed distal meteorites (WIS 91600, Tagish Lake and CI chondrites) argue that the CM, CO, and CR chondrites contain micrometer-scale dust and ice that originated in the distal solar system.